Status and trends of the employment in the financial institutions in Poland - Grzywińska-Rąpca, Małgorzata; Markowski, Lesław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The financial sector is one of the most important elements of socio-economic system of each country. The research work is employment in this sector focusing financial activities insurance and other activities supporting these activities. The aim of the study was to examine the level of employment in the financial sector in spatial terms (voivodship) in the period 2005–2014 using methods of multivariate statistical analysis. The attention was also drawn to the trends in the structure of employment in the financial sector between the voivodships and the same size of the number of employees in individual voivodship. The classification results indicate the geographical division of the country in terms of number of firms in the sector of finance and insurance. Data for the country also show a significant growing trend of employees in the financial sector. However its high directional coefficient is conditioned by very strong growing trend occurring in Mazowieckie much slower trend in the provinces of Dolnośląskie, Pomorskie, and Śląskie. For most voivodships tendency models indicates a negative statistically significant trend of the studied phenomenon.

Sektor finansowy stanowi jeden z najważniejszych elementów systemu społeczno-ekonomicznego każdego kraju. Przedmiotem badań w pracy jest wielkość zatrudnienia w tym sektorze skupiającym działalność finansową, ubezpieczeniową oraz pozostałą działalność wspomagającą powyższe działalności. Celem pracy było zbadanie poziomu zatrudnienia w sektorze finansowym w ujęciu przestrzennym (województwa) w latach 2005–2014 przy użyciu metod wielowymiarowej analizy statystycznej. Zwrócono również uwagę na trendy w strukturze zatrudnienia w sektorze finansowym między województwami, jak i samej wielkości liczby zatrudnionych w poszczególnych województwach. Dane dla kraju pokazują również na istotny rosnący trend wielkości zatrudnienia w sektorze finansowym. Jednakże jego wysoki współczynnik kierunkowy warunkowany jest bardzo silnym trendem wzrostowym, mającym miejsce w województwie mazowieckim, znacznie wolniejszym trendem w województwach dolnośląskim, pomorskim i śląskim. W przypadku większości województw bowiem, modele funkcji trendu wskazują na ujemną, statystycznie istotną tendencję rozwojową badanego zjawiska. Wyniki klasyfikacji wskazują na geograficzny podział kraju pod względem liczby podmiotów w sektorze finansów i ubezpieczeń.
Keywords: the financial sector; employment; k-means classification; trends; sektor finansowy; zatrudnienie; metoda k-średnich; modele trendu